2013
DOI: 10.1017/s1461145712001642
|View full text |Cite
|
Sign up to set email alerts
|

Olanzapine treatment of adolescent rats alters adult reward behaviour and nucleus accumbens function

Abstract: Antipsychotic drugs are increasingly used in children and adolescents to treat a variety of psychiatric disorders. However, little is known about the long-term effects of early life antipsychotic drug (APD) treatment. Most APDs are potent antagonists or partial agonists of dopamine (DA) D2 receptors ; atypical APDs also have multiple serotonergic activities. DA and serotonin regulate many neurodevelopmental processes. Thus, early life APD treatment can, potentially, perturb these processes, causing long-term b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 70 publications
4
45
1
Order By: Relevance
“…This difference in treatment age may be critical to the different results observed, with the antagonistic actions of Olanzapine treatment during the critical neurodevelopmental period previously found to result in long-term alterations to NT functioning, including the DA and 5-HT NT systems (Vinish et al 2012;Milstein et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference in treatment age may be critical to the different results observed, with the antagonistic actions of Olanzapine treatment during the critical neurodevelopmental period previously found to result in long-term alterations to NT functioning, including the DA and 5-HT NT systems (Vinish et al 2012;Milstein et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Although the effects of childhood/adolescent APD use on adult behaviours is unknown in a clinical setting, current animal studies have shown that early drug treatment for a period of up to 4 weeks can result in various significant alterations in the dopaminergic and serotonergic pathways in the brain long-term (Maciag et al 2006;Moran-Gates et al 2006;Vinish et al 2012;Milstein et al 2013;Varela et al 2014), including permanent changes in the distribution of NT receptors and dendritic architecture (Maciag et al 2006;Moran-Gates et al 2006;Milstein et al 2013), with minimal evidence of the direct effects on behaviour. Alterations to the production, transport and binding of DA and 5-HT in the cortical and striatal brain regions have already been directly linked to changes in behavioural attributes, including locomotor activity levels along with depressive-like and anxiety-like behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies have also illustrated that application of APD during adolescence, a critical period for neurodevelopment, can stimulate neuronal and behavioral functional changes that are reflected in adulthood (Vinish et al , 2013). Adolescent rats chronically exposed to the atypical APD olanzapine (OLZ) therapy released significantly less DA upon stimulation during adulthood than vehicle treated rats.…”
Section: Introductionmentioning
confidence: 99%
“…Recent preclinical studies of adolescent APD treatment have attempted to achieve a more clinically comparable pharmacokinetic profiles through the use of oral administration via cookie dough (three times a day) (De Santis et al 2016;Lian et al 2015;Lian et al 2016) or drinking water Vinish et al 2013;Xu et al 2015). Yet, only in one of these studies, plasma concentration of APD achieved was examined .…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…A few preclinical studies over the past five years have also started to examine long-term neurobiological consequences of adolescent treatment with atypical APDs (De Santis et al 2016;Milstein et al 2013;Qiao et al 2013;Vinish et al 2013). For example, adolescent treatment with olanzapine has been shown to induce long-term deficits in behaviour in adulthood, such as alterations in working memory, fear conditioning, reward behaviour (to amphetamine) and anxiety/depression-related behaviour, as well as changes in neurotransmission in the NAc, and dendritic spine pruning in other major brain regions (Brooks et al 2016;De Santis et al 2016;Milstein et al 2013;Xu et al 2015).…”
Section: Introductionmentioning
confidence: 99%